GENRE COMPOSITION OF GUTSUL FOLK - Kyrchiv, R.I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The features of the genre system of folk songs tradition of gutsuls are considered in the article. The winter is analysed, spring, summer and autumn cycles. It is indicated on popularity of separate genres: songs-chronicles, Colomyicas, history and toponymy translations and stories of mythological and fantastic-adventure character.